Pengembangan Sistem Informasi Lab Vokasi IPB (SILVI) Modul Bebas Administrasi - Wicaksono, Aditya; Mindara, Gema Parasti; Yulianti, Wina (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
One of the graduation requirements for students at the IPB University Vocational School is to have an Administrative Free Certificate. The letter is a unified approval from all Persons in Charge of the Laboratory and Library of SV IPB which explains that the student does not have a loan and is not receiving disciplinary sanctions from the Discipline, Student Affairs and Alumni Commission. The large number of prospective graduates every year causes a long queue in making the Certificate of Administrative Freedom if the submission is done manually to each Person in Charge of the Lab. The purpose of this research is to develop the IPB Vocational Lab Information System (SILVI) by adding an Administrative Free Module. The methodology used in this study is the Prototype Method. The stages carried out in the prototype method are communication, quick plan, modeling quick design, construction of prototype, and deployment delivery & feedback. Based on the feasibility test of the system, 100% of the features run without any errors, so it can be concluded that SILVI can be used properly.